EXTH-34. G-QUADRUPLEX DNA DRIVES GENOMIC INSTABILITY AND REPRESENTS A TARGETABLE MOLECULAR ABNORMALITY IN ATRX-DEFICIENT MALIGNANT GLIOMA. (5th November 2018) - Wang, Yuxiang; Yang, Jie; Danussi, Carla; Riggins, Gregory; Sulman, Erik; Chan, Timothy; Huse, Jason T
Abstract: Mutational inactivation of ATRX (a-thalassemia mental retardation X-linked) represents a defining molecular alteration in large subsets of malignant glioma. ATRX encodes a chromatin binding protein widely implicated in epigenetic regulation and remodeling. However, multiple studies have also associated its loss in cancer with replication stress, DNA damage, and copy number alterations (CNAs). The mechanisms by which ATRX deficiency drives this global genomic instability remain unclear. Here we report that ATRX inactivation in isogenic glioma model systems induces replication stress and DNA damage by promoting the formation of deleterious G-quadruplex (G4) secondary structure in DNA. Moreover, these effects are associated with the acquisition of disease-relevant CNAs over time. Prior work has linked G4s with genomic instability as well as CNAs in cancer. We then demonstrate, both in vitro and in vivo, that chemical G4 stabilization with CX-3543 (Quarfloxin) selectively enhances cell death in ATRX deficient isogenic cell lines as well as ATRX -mutant primary glioma stem cells derived from patients. Finally, we show that G4 stabilization synergizes with other DNA-damaging therapies, including ionizing radiation, in the ATRX-deficient context. Our findings clarify distinct mechanisms by which DNA secondary structure influences ATRX-deficient glioma pathogenesis and indicate that G4-stabilization may represent and attractive therapeutic strategy for the selective targeting of ATRX -mutant cancers. Opportunities for the development of radiosensitization approaches based on G4-stabilization are particularly intriguing, as ionizing radiation remains among the most effective non-surgical treatments for malignant glioma.